The Effectivecness of Communicative Language Teaching (CLT) on Students Speaking Abylity at SMAN 1 Rejotangan - Muhammad Nur Aziz; Moh. Hanafi (International Journal of Sustainable Applied Sciences, 2024)
The main objective of learning English is to use it to communicate. Teachers must have good teaching methods to solve the problems students face in learning English.  Communicative Language Teaching is one of the methods that suits the goal of language teaching, especially in teaching speaking. Thus, the research objective was to know the effectiveness of communicative language teaching on students' speaking abilities. The researcher used a quantitative research design that was carried out using a pre-experimental design (pre-test and post-test). The population of this research is tenth-grade students of SMAN 1 Rejotangan Tulungagung. The sample in this study consisted of students from class tenth G, totaling 36 students. The researcher chose 20 tenth-grade students in SMAN 1 Rejotangan Tulungagung for this research. The instrument was an oral test. The data was analyzed using descriptive statistical analysis, and the hypothesis was tested using a paired Sample T-test. The average post-test score is higher than the average post-test score on the initial test (80.40 > 75.45). Furthermore, the significant value obtained is lower than the significance level (0.000 < 0.05). Thus, the tenth-grade students of SMAN 1 Rejotangan have better speaking ability after being taught using the CLT strategy.